The electric field and dopant distribution in p-i-n structures observed by ionisation potential (dopant contrast) microscopy in the HRSEM - Grunbaum, E; Barkay, Z; Shapira, Y; Barnham, K; Bushnell, D; Ekins-Daukes, N; Mazzer, M; Wilshaw, P (2005)
The method of ionisation potential (dopant contrast) microscopy in the HRSEM is applied to the study of the electric field distribution in p-i-n structures used as quantum well solar cells. Our results show a secondary electron signal which varies between the different layers, being greatest in the p-type and smallest in the n-type regions respectively. The stacks of 8 nm wide quantum wells and their corresponding barriers are clearly distinguished in the intrinsic region of the devices. In-situ observation of reverse biased structures has been performed to determine the effect of bias on the potential distribution within the devices.